Spot oil, netbacks and petroleum futures : the emergence of a new oil market - Fesharaki, Fereidum (Economist Publications LondonGB, 1986)
Provides a detailed analysis of the evolution and dynamics of the oil market; spot trading, futures trading, and the netback system. Shows the complex linkages and interactions between the various segments of the oil market. Provides a detailed chart showing how the oil market got into its present position, and where it is moving next. Discusses topics such as petroleum spot trading, spot related deals, netback pricing contracts, the role of petroleum spot prices, oil futures markets and spot trading, and OPEC, spot and futures trading.